EFFECTS OF CONTEXTUAL TEACHING AND LEARNING WITH POP-UP BOOKS ON ELEMENTARY STUDENTS' MATHEMATICAL CONCEPT UNDERSTANDING - Gita Aprilia; Hisny Fajrussalam; Teten Ginanjar Rahayu (EMTEKA: Jurnal Pendidikan Matematika, 2026)
This study is motivated by the low ability of students to understand mathematical concepts. One of the internal factors contributing to students' low mathematical conceptual understanding is their negative perception of mathematics as a subject. Mathematics is often perceived as difficult, uninteresting, and monotonous, leading students to believe that the learning materials are challenging to comprehend. Such perceptions may reduce students' motivation and engagement in the learning process, which ultimately results in lower levels of mathematical conceptual understanding and overall academic achievement. Efforts which can be conducted to overcome this problem are to hold interactive learning and the use of innovative learning models and media. The learning models which were used were the Contextual Teaching and Learning model assisted by pop-up book media. The aims of this study is to determine the effect of the Contextual Teaching and Laerning model assisted by pop-up book media on students' mathematical concept understanding abilities; besides, to determine the differences in the improvement of mathematical concept understanding abilities between students who implement the Contextual Teaching and Laerning model and Problem Based Learning. This study used a quasi-experimental method with a Non-equivalent Control Group Design. The findings of the study indicate that the Contextual Teaching and Learning (CTL) model has a significant positive effect on students' mathematical conceptual understanding, as evidenced by the improvement in elementary school students' learning outcomes. Penelitian ini dilatarbelakangi oleh rendahnya kemampuan pemahaman konsep matematis siswa. Salah satu faktor internal yang mempengaruhi rendahnya kemampuan pemahaman konsep matematis siswa adalah pikiran negatif siswa terhadap pelajaran matematika itu sendiri. Pelajaran matematika masih dianggap mata pelajaran yang sulit dan menakutkan karena tidak menarik, membosankan dan sulit dipahami oleh peserta didik yang menyebabkan rendahnya hasil belajar siswa. Salah satu upaya yang dapat dilakukan untuk mengatasi permasalahan tersebut adalah mengelar pembelajaran yang interaktif dan penggunaan model serta media pembelajaran yang inovatif. Salah satu model pembelajaran yang dapat digunakan adalah model Contextual Teaching and Learning berbantuan media pop-up book. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran Contextual Teaching and Laerning berbantuan media pop-up book terhadap kemampuan pemahaman konsep matematis siswa serta mengetahui perbedaan peningkatan kemampuan pemahaman konsep matematis antara siswa yang belajar menggunakan model Contextual Teaching and Laerning dan Problem Based Learning. Penelitian ini menggunakan metode kuasi eksperimen dengan desain Non-equivalent Control Group Design. Hasil penelitian menunjukkan bahwa model pembelajaran Contextual Teaching and Learning memiliki pengaruh yang signifikan terhadap kemampuan pemahaman konsep matematis siswa dilihat dari peningkatan hasil belajar siswa sekolah dasar.